2018
DOI: 10.1016/j.celrep.2018.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Duodecuple Mutant of PYL ABA Receptors Reveals PYL Repression of ABA-Independent SnRK2 Activity

Abstract: SUMMARYAbscisic acid (ABA) is an important phytohormone controlling responses to abiotic stresses and is sensed by proteins from the PYR/PYL/RCAR family. To explore the genetic contribution of PYLs toward ABA-dependent and ABA-independent processes, we generated and characterized high-order Arabidopsis mutants with mutations in the PYL family. We obtained a pyl quattuordecuple mutant and found that it was severely impaired in growth and failed to produce seeds. Thus, we carried out a detailed characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
146
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(172 citation statements)
references
References 43 publications
4
146
0
5
Order By: Relevance
“…Such constructs target all loci simultaneously in every transgenic event, so that high‐order mutants are generated ultimately, however it would be difficult to obtain a single or low‐order mutant by such vector. Even if an event of the desired genotype were identified, the CRISPR/Cas9 system would keep targeting other loci until all genes were targeted (Xing et al ., ; Zhao et al ., ). By contrast with multiplex vector, the genotypes of transgenic events with combinations of CRISPRs are more predictable.…”
Section: Discussionmentioning
confidence: 97%
“…Such constructs target all loci simultaneously in every transgenic event, so that high‐order mutants are generated ultimately, however it would be difficult to obtain a single or low‐order mutant by such vector. Even if an event of the desired genotype were identified, the CRISPR/Cas9 system would keep targeting other loci until all genes were targeted (Xing et al ., ; Zhao et al ., ). By contrast with multiplex vector, the genotypes of transgenic events with combinations of CRISPRs are more predictable.…”
Section: Discussionmentioning
confidence: 97%
“…As a caveat, even though the phylogenetic analysis clearly identifies the involved genes as orthologs, experimental validation of the functional orthology as well as validation of the beneficial effects of additional genes will be important next steps. It is interesting that one of the Esa‐ and Aly ‐upregulated proteins, PYL6, was the only remaining ABA receptor in a duodecuple mutant, and is able to partially activate ABA transcriptional responses (Zhao et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with the observation in Arabidopsis of higher response activation by OST1 with non‐functional ABA‐box (Yoshida et al , ). The release of SnRK2s from attenuation is also modulated by ABA receptors as indicated by the hyper‐activation of SnRK2s in a multiple RCAR‐deficient Arabidopsis mutant under osmotic stress (Zhao et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of Arabidopsis mutants deficient in multiple SnRK2s indicated that subgroup III members act together with SnRK2s of subgroups I and II independently of ABA in the osmotic stress response pathway (Boudsocq et al , ; Fujii & Zhu, ; Fujii et al , ). A negative feedback of ABA signaling onto osmotic stress responses was inferred by the hyper‐activation of SnRK2s in an Arabidopsis mutant deficient in multiple ABA receptors (Zhao et al , ). Osmotic stress is known to trigger ABA‐independent and ABA‐dependent signaling pathways (Yoshida et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation